Safeguarding the unknown: performance measurement, academic agency and the meaning of research quality in practice - Bedford David S.; Granlund Markus; Lukka Kari (Emerald, 2025)
Purpose
The authors examine how performance measurement systems (PMSs) and academic agency influence the meaning of research quality in practice. The worries are that the notion of research quality is becoming too simplistically and narrowly determined by research quality's measurable proxies and that academics, especially manager-academics, do not sufficiently realise this risk. Whilst prior literature has covered the effects of performance measurement in the university sector broadly and how PMSs are mobilised locally, there is only little understanding of whether and how PMSs affect the meaning of research quality in practice.
Design/methodology/approach
The study is designed as a comparative case study of two university faculties in Finland. The role of conceptual analysis plays a notable role in the study, too.
Findings
The authors find that manager-academics of the two examined faculties have rather similar conceptual understandings of research quality. However, there were differences in the degree of slippage between the "espoused-meaning" of research quality and "meaning-in-practice" of research quality. The authors traced these differences to how the local PMS and manager-academics' agency relate to one another within the context of increasing global and national performance pressures. The authors developed a tentative framework for the various "styles of agency". This suggests how the relationship between the local PMS and manager-academics' exerted agency shapes the "degrees of freedom" of the meaning of research quality in practice.
Originality/value
Given that research quality lies at the heart of academic work, the authors' paper indicates that exploring the three matters - performance measurement, the agency of manager-academics and the meaning of research quality in practice - in combination is crucial for the sustainability of the academe. The authors contribute to the literature by detailing the way in which local PMS and manager-academics' agency have material impacts on what research quality means in practice. The authors conclude by highlighting the pressing need for manager-academics to exercise the agency in efforts to safeguard a broad and pluralistic understanding of research quality in practice.